Ultraviolet photosensor based on few layered reduced graphene oxide nanosheets - Shelke, Nitin T.; Karche, B. R. (Applied Surface Science, 2017)
Reduced graphene oxide (RGO), a two-dimensional (2D) system, has attracted much interest in photonic applications owing to its ability to absorb light over a broad wavelength. This leads to several studies on RGO-based photosensors. In this paper, chemical oxidation of graphite was carried out at room temperature for the preparation of large area reduced graphene oxide using a modified Hummer's method. The as-prepared reduced graphene oxide was characterized by XRD, Raman spectroscopy, FESEM, and TEM to confirm the absence of impurities and to ascertain their morphology. In addition, the as-prepared reduced graphene oxide for its possible application as UV photosensor is reported. The electric and optoelectronic properties of RGO based UV photosensor shows a fast response and recovery time of 1 s and 3 s; high photoresponsitivity (3.74AW(-1)) and quantum efficiency (1274%) indicating that the graphene oxide is an important material for high performance photosensor. This work demonstrates the ultrafast photoresponse with high photoresponsivity, proving its potential as a promising material for optoelectronic devices. 2016 Elsevier B.V. All rights reserved.